Relationship between spiritual leadership and organizational commitment in the oil and gas industry / Mohd Afifie Mohd Alwi, Nurhani Anwar and Ahmad Haziq Ismail - Mohd Alwi, Mohd Afifie; Anwar, Nurhani; Ismail, Ahmad Haziq (2013)
The notion of spirituality in organization has sparked a considerable amount of interest since the last decade with scarcity of research on the particular topic in the Malaysian setting. The aim of this paper is to examine the relationship between spiritual leadership and organizational commitment in the oil and gas industry as well as to assess the moderating role of religiousness among leaders. The research also attempts to investigate the perception of employees towards organizational commitment from different demographic factors. The research adopts Fry's (2003) causal model of spiritual leadership whereby four elements of vision, altruistic love, calling/meaning and membership have been considered for empirical study. A questionnaire survey was conducted in selected oil and gas companies in Terengganu using mainly quota sampling method. Data were gathered from 203 respondents for hypothesis testing. Descriptive statistics were reported, followed by reliability analysis, Pearson correlation, T -test, multiple regression, Kruskal-Wallis and partial correlation analysis. Findings showed that all of the elements of spiritual leadership have significant relationships with organizational commitment whereby altruistic love appears to have the highest strength of correlation. Further inclusion of religiousness as a moderator weakens the relationship between the variables of the study. Differences in race among the respondents contribute to the significance of perception towards organizational commitment. Thus, the study suggests that companies in the oil and gas industry should consider nurturing spiritual leaders for increased commitment while also placing emphasis on other extrinsic rewards. Future research might consider other elements of spirituality or different construct of religiousness in a varied working environment.